PERANCANGAN TATA LETAK FASILITAS PERPUSTAKAAN SEKOLAH TINGGI TEKNOLOGI CIPASUNG - Wahyu Teri Aripin; Dini Ramdaniyah (Cipasung Techno Pesantren: Jurnal Ilmiah, 2022)
Libraries are a source of information and learning for the community. In their daily life, people need the availability and services of information that can be obtained easily and quickly. Activities carried out in the library need to be well coordinated so that there is no confusion. The efficiency and effectiveness of the services provided by the library to its users is largely determined by the placement of service work units in the library. The services provided are not only determined by the availability or size of the room, but the most important thing is that the placement of the services is arranged so that it shows the best pattern of work and supervision. This study aims to determine how to design the layout of the library room at STT Cipasung. This type of research is to use the principle of an open system (open access). Data collection was done by interview, and observation. Interviews were conducted with the library staff of STT Cipasung. The result of the study are in the form of room arrangement and library design proposed in the form of library layout design drawings, for the proposed conditions based on the location plan of the STT Cipasung library room. Finally, from the calculation of the room, it can be concluded that the layout of the STT Cipasung library has a visitor capacity of 25 people.